Desain Website Gaya Hidup Sehat Menggunakan Metode Design Thinking - Faila Nadhifatul Aryza; Djuniadi Djuniadi; Ahmad Fashiha Hastawan (Politeknik Negeri Batam, 2026)
Healthy lifestyles have become a focus in the modern era. This activity is an effort to balance human needs and environmental sustainability. However, public awareness of their role in adopting a healthy lifestyle is still lacking. Limited education and access to information can be a main reason. Based on this issue, the researcher created a healthy lifestyle website design as an educational medium for the public. The target audience of this media includes three generations: Millennials, Gen Z, and Gen Alpha. These three generations are potential agents of change in promoting a healthy lifestyle. The design creation uses the design thinking method. This method includes five stages: empathize, define, ideate, design, and test. After the website design was made, the researcher validated the design using the System Usability Scale (SUS) method. The SUS score calculation from 35 respondents resulted in a value of 65.86. The score above is still far from the maximum score of 100. So, the healthy lifestyle website design still needs some improvement.